2010
DOI: 10.1016/j.ydbio.2010.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Junb family proteins by the Jun N-terminal kinase supports tissue regeneration in zebrafish

Abstract: Tissue regeneration is fundamental for multi-cellular organisms to maintain their integrity, but the competence of tissue restoration is different depending on tissues, species, and ages. In spite of the recent progresses of the molecular basis of regeneration, little is known about its regulative processes. We previously identified the junb and junb-like (junbl) as transcripts induced in response to tissue injury in zebrafish. It has been demonstrated that the mammalian JunB is not phosphorylated by the Jun N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 49 publications
4
52
0
Order By: Relevance
“…5A,B). Significantly, the expression of junbl, an earlier blastema marker (Ishida et al, 2010), was strongly and ectopically upregulated in and around the blastema (Fig. 5C,D), suggesting that fgf20a overexpression causes mesenchymal cells to acquire the distal blastema identity.…”
Section: Fgf20a Overexpression Induces Distal Blastema Markersmentioning
confidence: 94%
See 2 more Smart Citations
“…5A,B). Significantly, the expression of junbl, an earlier blastema marker (Ishida et al, 2010), was strongly and ectopically upregulated in and around the blastema (Fig. 5C,D), suggesting that fgf20a overexpression causes mesenchymal cells to acquire the distal blastema identity.…”
Section: Fgf20a Overexpression Induces Distal Blastema Markersmentioning
confidence: 94%
“…Immunostaining was performed on tissue sections according to a standard protocol (Ishida et al, 2010). Polyclonal anti-DsRed antibody (632393, Invitrogen) and anti-p63 antibody (ab97865, Abcam) were used at 1:1000.…”
Section: Immunostaining and Histological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Amputated zebrafish embryos obtained from a ptena +/− ptenb −/− in‐cross were fixed at 3 h post amputation (hpa) and subjected to in situ hybridization for detection of mmp9 transcription, which is a marker for the wound epithelium (Yoshinari, Ishida, Kudo, & Kawakami, 2009), and junbb and and1 transcription, both of which have previously been shown to be upregulated in the blastema (Thorimbert et al., 2015; Yoshinari et al., 2009). In fact, junbb expression is maintained well into the initial stage of regenerative outgrowth, indicating that junbb is a definitive distal blastema marker (Ishida, Nakajima, Kudo, & Kawakami, 2010). Both mmp9 and junbb were clearly induced by amputation of the caudal fin‐fold, and ptena −/− ptenb −/− mutant embryos expressed mmp9 and junbb to a similar extent as their siblings (Fig.…”
Section: Blastema Formation Marker Suggests That the Initial Responsementioning
confidence: 99%
“…In invertebrates, it has been shown that apoptotic cells release Wnt and BMP signals that are directly responsible for compensatory proliferation in injured Drosophila imaginal discs [18] and head regeneration in hydra [8]. In mammals, it has been shown that during the process of apoptosis, activated caspases stimulate Ca2+-independent phospholipase A2 (iPLA2) to trigger the production of prostaglandin (PGE2), which in turn induces compensatory proliferation [19,20]. This induction of cell proliferation, via apoptosis/PGE2, near the dying cells is essential for skin wound healing and liver regeneration in mice.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%